Factors influencing participation in fecal occult blood testing to screen for colorectal cancer in Australia: a scoping review protocol. (January 2018) - Lee, Simone; Miller, Andrea
Abstract : Review question: The objective of this scoping review is to examine and map the evidence on the range of factors influencing a person's decision to screen or not screen for colorectal cancer using a fecal occult blood test (FOBT) in Australia, with the view to identifying gaps in the research and informing appropriate questions for future systematic reviews. The question of this review is: what evidence is available around the barriers and facilitators that influence an individual's decision to screen or not screen for colorectal cancer using a fecal occult blood test in Australia?